BERTRAND MATE OF BIHARMONIC CURVES IN THE SPECIAL THREE-DIMENSIONAL KENMOTSU MANIFOLD K WITH ?-PARALLEL RICCI TENSOR - Korpinar, Talat; Turhan, Essin (Inst Applied Mathematics, 2011)
In this paper, we study biharmonic curves in the special three-dimensional Kenmotsu manifold K with 77 eta-parallel Ricci tensor. We characterize the biharmonic curves in terms of their curvature and torsion. Moreover, we construct parametric equations of Bertrand mate of biharmonic curves in the special three-dimensional Kenmotsu manifold K with 77 eta-parallel Ricci tensor.
Keywords: biharmonic curve; Kenmotsu manifold; Bertrand mate